Impact of Competency, Training, Employee Commitment on Performance at the Regional Secretariat of Jember Regency - Galih Galih; Audi Ryan Setiawan; Ronald Farid Maruf; Nurul Qomariah; Nursaid Nursaid (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This research aims to analyze the impact of competency, training, commitment on employee performance at the Jember Regency Regional Secretariat. The population in this study were all employees at the Regional Secretariat of Jember Regency, totaling 60 employees and all of them were used as research samples. Descriptive data analysis was used to determine the description of respondents. Validity tests and reliability tests were carried out to test whether the research questionnaire met the requirements for conducting research. Hypothesis testing is carried out to test the influence of the independent variable on the dependent variable. The results of the analysis show that competence, training, commitment to employee performance at the Regional Secretariat of Jember Regency.